HALAL TOURISM AMONG GEN Z: ANALYZING THE EFFECT OF HALAL AWARENESS AND DESTINATION TRUST ON VISIT INTENTION WITH RELIGIOSITY AS A MEDIATOR - Rika Ra'idah Dwicahyani; Anindya Heidi Shafira; Noveri Maulana; Siska Mandalia (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
This study investigates the factors shaping Generation Z’s interest in halal tourism, with a focus on evaluating the alignment of Java Island’s destinations—Indonesia’s most populous region—with halal standards. Emphasizing the necessity for heightened awareness of halal compliance in tourism, data were gathered from 416 Indonesian respondents planning trips to Java. Structural equation modeling via SmartPLS analyzed the relationships among halal awareness, destination trust, religiosity, and visit intention. Results demonstrated that destination trust exerted the strongest direct influence on visit intention, surpassing halal awareness. Furthermore, religiosity significantly mediated the relationship between destination trust and visit intention, validating the role of religious values shape travel decisions. These insights highlight that halal tourism appeal hinges not only on transparent halal practices but also on fostering trust and integrating religiosity into destination planning. The study advocates for targeted strategies to enhance halal literacy and reinforce ethical tourism frameworks tailored to Gen Z’s evolving needs.